Beyond Mechanical Recycling: Giving New Life to Plastic Waste - Vollmer, Ina; Jenks, Michael J. F.; Roelands, Mark C. P.; White, Robin J.; Harmelen, Toon; Wild, Paul; Laan, Gerard P.; Meirer, Florian; Keurentjes, Jos T. F.; Weckhuysen, Bert M. (Angewandte Chemie International Edition, 2020)
Increasing the stream of recycled plastic necessitates an approach beyond the traditional recycling via melting and re‐extrusion. Various chemical recycling processes have great potential to enhance recycling rates. In this Review, a summary of the various chemical recycling routes and assessment via life‐cycle analysis is complemented by an extensive list of processes developed by companies active in chemical recycling. We show that each of the currently available processes is applicable for specific plastic waste streams. Thus, only a combination of different technologies can address the plastic waste problem. Research should focus on more realistic, more contaminated and mixed waste streams, while collection and sorting infrastructure will need to be improved, that is, by stricter regulation. This Review aims to inspire both science and innovation for the production of higher value and quality products from plastic recycling suitable for reuse or valorization to create the necessary economic and environmental push for a circular economy. Plastic fantastic: Plastic can rise again and again as a new product. Researchers now know methods with which new plastics can be produced from 100 % recycled material, products that can even be used for food applications. This development is possible thanks to chemical recycling, through which polymer chains are first broken to then be reformed into new molecules, such as plastics but also other chemicals.